Eighth International Congress on Spondyloarthritis - Anna Georgiyevna Bochkova (Современная ревматология)
In 1998 the First Congress of the European Ankylosing Spondylitis (AS) Working Group was held and attended by 9 leading experts from Germany and the Netherlands. Much scientific and organizational work has been done for 14 years, causing all spondyloarthritis (SA) studies to be coordinated and discussed by the working group experts thrice a year. A regular SА congress is held at Ghent, Belgium, every 2 years. In 2009, the working group was renamed the Assessment of SpondyloArthritis international Society (ASAS) having about 90 members from more than 30 countries. The results of the society’s activity were new classification criteria for axial (2009) and peripheral (2011) SA, criteria for authentic sacroiliitis and spondylitis according to MRI data; guidelines for AS treatment, those for the use TNF inhibitors in SA, and the Ankylosing Spondylitis Disease Activity Score.